EVALUASI KEMANANAN SISTEM INFORMASI PASDEAL BERDASARKAN INDEKS KEAMANAN INFORMASI (KAMI) ISO/IEC 27001:2013 - Yahya Dwi Wijaya (Program Studi Sistem Informasi, Universitas Banten Jaya, 2021)
Information systems are a valuable asset for business actors, one of which is engaged in e-commerce. Pasdeal is a credit distributor and server service that implements an e-commerce information system. The use of information systems in the field of sales or electronic commerce is considered efficient because it has become a platform for media and services and new and unique capabilities that are not found in the physical world. Information security factor is a very important aspect to consider considering the performance of ICT governance. For this reason, information systems need an information security evaluation in order to find out the gaps and deficiencies in information security in the information system. The KAMI index is a reference tool to evaluate the level of readiness of information system security in an organization. Evaluation is carried out on various areas that are the target of information security implementation based on the ISO/IEC 27001:2013 standard. Based on the results of the KAMI index assessment, it was found that Pasdeal got a score of 591 points from the application of the ISO 27001 standard with a pretty good predicate.